UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGAN PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION DILENGKAPI QUIZIZZ - Ulfa, Fadhilla; D, Rahmawati; Yogica, Relsas; Rahmatika, Helsa (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
Biology learning in high school still faces challenges in achieving optimal learning outcomes, especially in complex materials such as the circulatory system. This study aims to analyze the effect of implementing the Cooperative Integrated Reading and Composition (CIRC) cooperative learning model equipped with Quizizz on student learning outcomes in circulatory system material. The research method used was Classroom Action Research (CAR) using Kurt Lewin's model with four stages: planning, action, observation, and reflection. The research was conducted at SMAN 2 Batusangkar in November 2024 with 34 students of class XI.F3 as research subjects. Data analysis techniques used descriptive quantitative analysis to measure the improvement of learning outcomes from pre-cycle to cycle II. The results showed significant improvement in cognitive aspects with average scores increasing from 61.6 (pre-cycle) to 74.7 (cycle I) and 88 (cycle II), and learning completeness increased from 14.71% to 97.06%. The attitude aspect also improved from 35.1% (pre-cycle) to 86.4% (cycle II). The combination of CIRC model with Quizizz platform proved effective in creating active, collaborative, and meaningful learning in improving students' understanding of biology concepts and positive attitudes.